AKTIVITAS FISIK BERSEPEDA DAN KEBUGARAN FISIK LANSIA BINA KELUARGA LANSIA DESA GAYAMAN - Kusuma, Yudha Laga Hadi; Astuti, Leni (MEDICA MAJAPAHIT, 2023)
Physical fitness is a person's body's ability to carry out daily tasks or work without causing significant fatigue. In addition, physical activity has a positive impact on energy balance and weight control. Thus, individual fitness and productivity levels increase because the body functions effectively and has sufficient energy. The aim of this research was to determine the physical activity of cycling and the physical fitness of the elderly in Gayaman Village Elderly Family Development. This research uses a cross sectional research design. The population in this study was all 60 cycling participants at Bina Keluarga Lansia (BKL) with a purposive sampling technique. Data was collected using the Physical Activity and Physical Fitness questionnaire. The collected data was processed and analyzed using the Spearman Rank test. The research results showed that the majority of respondents carried out the physical activity of cycling regularly, 43 (71.7%), the majority of respondents had moderate physical fitness, 42 (70%). The p value obtained was 0.000 < α 0.05, which means there is a relationship between the physical activity of cycling and the physical fitness of the Elderly Family Development (BKL) participants in Gayaman Village, Mojokerto. Good fitness will certainly benefit someone, especially the elderly, when carrying out their daily activities both outside and at home. To be able to have good fitness, the family should provide encouragement (motivation) and facilities for the elderly to be willing and responsible for their physical fitness.Physical fitness is a person's body's ability to carry out daily tasks or work without causing significant fatigue. In addition, physical activity has a positive impact on energy balance and weight control. Thus, individual fitness and productivity levels increase because the body functions effectively and has sufficient energy. The aim of this research was to determine the physical activity of cycling and the physical fitness of the elderly in Gayaman Village Elderly Family Development. This research uses a cross sectional research design. The population in this study was all 60 cycling participants at Bina Keluarga Lansia (BKL) with a purposive sampling technique. Data was collected using the Physical Activity and Physical Fitness questionnaire. The collected data was processed and analyzed using the Spearman Rank test. The research results showed that the majority of respondents carried out the physical activity of cycling regularly, 43 (71.7%), the majority of respondents had moderate physical fitness, 42 (70%). The p value obtained was 0.000 < α 0.05, which means there is a relationship between the physical activity of cycling and the physical fitness of the Elderly Family Development (BKL) participants in Gayaman Village, Mojokerto. Good fitness will certainly benefit someone, especially the elderly, when carrying out their daily activities both outside and at home. To be able to have good fitness, the family should provide encouragement (motivation) and facilities for the elderly to be willing and responsible for their physical fitness.